Preclinical evaluation of the neutralizing ability of a monospecific antivenom for the treatment of envenomings by Bothrops lanceolatus in Martinique. (15th June 2018) - Resiere, Dabor; Arias, Ana Silvia; Villalta, Mauren; Rucavado, Alexandra; Brouste, Yannick; Cabié, André; Névière, Rémi; Césaire, Raymond; Kallel, Hatem; Mégarbane, Bruno; Mehdaoui, Hossein; Gutiérrez, José María
Abstract: Bothrops lanceolatus is an endemic viperid species in the Lesser Caribbean island of Martinique. Envenomings by this species are characterized by local and systemic effects, among which the development of thrombosis in various organs is the most severe complication. An experimental toxicological characterization of this venom was performed using in vivo mouse tests and various in vitro assays. The venom induced lethal, local and systemic hemorrhagic, edema-forming, myotoxic, thrombocytopenic, proteinase and phospholipase A2 activities. The preclinical efficacy of a batch of monospecific Bothrofav ® antivenom currently in use in Martinique was assessed. The antivenom was highly effective in the neutralization of all activities tested, in agreement with its described clinical efficacy. This batch of antivenom showed a higher preclinical efficacy as compared to a previous batch used in the past. Graphical abstract: Highlights: The toxicological profile of the venom of Bothrops lanceolatus from Martinique was studied. Venom induced lethal, hemorrhagic, myotoxic, edema-forming, and thrombocytopenic effects. The monospecific antivenom Bothrofav ® was effective in the neutralization of these effects. This batch of antivenom showed a higher potency than another batch previously used.